Milk intolerance, beta-casein and lactose - Pal, Sebely; Woodford, K.; Kukuljan, S.; Ho, S. (MDPI AG, 2015)
True lactose intolerance (symptoms stemming from lactose malabsorption) is less common than is widely perceived, and should be viewed as just one potential cause of cows’ milk intolerance. There is increasing evidence that A1 beta-casein, a protein produced by a major proportion of European-origin cattle but not purebred Asian or African cattle, is also associated with cows’ milk intolerance. In humans, digestion of bovine A1 beta-casein, but not the alternative A2 beta-casein, releases beta-casomorphin-7, which activates µ-opioid receptors expressed throughout the gastrointestinal tract and body. Studies in rodents show that milk containing A1 beta-casein significantly increases gastrointestinal transit time, production of dipeptidyl peptidase-4 and the inflammatory marker myeloperoxidase compared with milk containing A2 beta-casein. Co-administration of the opioid receptor antagonist naloxone blocks the myeloperoxidase and gastrointestinal motility effects, indicating opioid signaling pathway involvement. In humans, a double-blind, randomized cross-over study showed that participants consuming A1 beta-casein type cows’ milk experienced statistically significantly higher Bristol stool values compared with those receiving A2 beta-casein milk. Additionally, a statistically significant positive association between abdominal pain and stool consistency was observed when participants consumed the A1 but not the A2 diet. Further studies of the role of A1 beta-casein in milk intolerance are needed.